2017
DOI: 10.1093/infdis/jix279
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Overexpression During Endotoxin Tolerance Impairs the Adaptive Immune Response in Septic Patients via HIF1α

Abstract: Sepsis, among other pathologies, is an endotoxin tolerance (ET)-related disease. On admission, we classified 48 patients with sepsis into 3 subgroups according to the ex vivo response to lipopolysaccharide. This response correlates with the Acute Physiology and Chronic Health Evaluation (APACHE) II score and the ET degree. Moreover, the ET-related classification determines the outcome of these patients. Programmed cell death-ligand 1 (PD-L1) expression on septic monocytes is also linked with ET status. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 50 publications
7
58
0
Order By: Relevance
“…In accordance with our previous data, the biological activities described above are controlled by hypoxia-inducible factor-1α (HIF1α) expression ( 13 , 15 ). In this regard, HIF1α is the most important pathway for oxygen homeostasis in mammals ( 16 ).…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…In accordance with our previous data, the biological activities described above are controlled by hypoxia-inducible factor-1α (HIF1α) expression ( 13 , 15 ). In this regard, HIF1α is the most important pathway for oxygen homeostasis in mammals ( 16 ).…”
Section: Introductionsupporting
confidence: 88%
“…The discovery and characterisation of immune checkpoints (ICs) adds a new parallel window of study in which cell-to-cell interaction could have an important role beyond cancer pathologies ( 9 ). In this regard, we and others have already reported programmed death-ligand 1 (PD-L1) overexpression on sepsis monocytes ( 10 13 ), which was associated with risk stratification and mortality in these patients ( 14 ).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…The monocytes, a kind of antigen-presenting cells (APC), acted as instigators of T cell suppression in adaptive response by mediating the expression of inhibitory coreceptors such as programmed cell death protein 1 (PD-1) and cytotoxic T lymphocyte-associated protein 4 (CTLA4) [10,11]. The researches of Avendano-Ortiz et al [12] and Shalova et al [13] showed that hypoxia-inducible factor-1α (HIF-1α) regulated functional reprogramming of monocytes in sepsis to suppress T cells with inhibitory coreceptors, cytokines, and chemokines. It was also shown by Tsukamoto et al [14] that the myeloid-derived suppressor cells (MDSCs) were more suppressive in nature by upregulating the expression of PD-L1 to impair antigen-specific T cell priming and IgG production in sepsis.…”
Section: Introductionmentioning
confidence: 99%